Caribbean Report 20-03-1997 - Rowe, Yvette (anchor); Orr, Carol (correspondent); Douglas, Denzil (interviewee); Apples, John (interviewee); Jagan, Janet (interviewee); Norton, Michael (correspondent) (The British Broadcasting Corporation, 1997)
In this report, the Dutch Central Bank expresses concern about the unregulated pyramid schemes in Surinam. Next, Dr Denzil Douglas, Prime Minister of St Kitts and Nevis has expressed his disappointment at the World Trade Organisation interim report pointing toward support for the United States Challenge to the EU banana import regime. He also discusses the secession issue. Next, Guyana’s new Prime Minister, Janet Jagan says she will be staying with the policies of her late husband, Cheddi Jagan, especially his stance to wipe out corruption. In Haiti’s capital of Port-au-Prince, the general strike failed as few protestors smashed car windows, businesses opened in the suburbs and people defied threats of violence and walked to work. The report concludes with Stories of Caribbean interest appearing in the British press
1. Headlines (00:00-00:31)
2. The Dutch Central Bank expresses concern over unregulated pyramid investment schemes in Surinam. Joseph Paul Apples of the Dutch Central Bank is interviewed and Carol Orr reports (00:32-04:07)
3. The Prime Minister of St Kitts and Nevis, Dr. Denzil Douglas expresses his disappointment with the World Trade Organisation report on the EU banana import regime. Dr Denzil Douglas, Prime Minister of St Kitts and Nevis is interviewed (04:08-07:38)
4. Guyana's new Prime Minister, Janet Jagan pledges to stay with the policies of her late husband. Prime Minister of Guyana, Janet Jagan is interviewed (07:39-10:52)
Keywords: Dutch Central Bank.; Pyramid -- Surinam.; Interim report -- World Trade Organisation.; Secession -- Nevis.; Secession -- St Kitts.; Prime Minister -- Guyana.; Protest -- Haiti.; Strike -- Haiti.